ChatGPT As Management Tools For Organization Environment Analysis: Study From Indonesian Gen Y And Z - Andrew Wibisono; Yuli Kartika Dewi (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2025)
ChatGPT has become a valuable tool for individuals, offering an interactive platform to complete tasks with precision and efficiency capabilities often beyond traditional tools. As AI adoption grows rapidly, especially in Indonesia where ChatGPT ranks among the top-used platforms, there is a growing need to understand what drives its continued use, particularly among young digital natives. This study aims to explore behavioral factors habit formation and perceived information accuracy that influence users' intention to adopt ChatGPT within educational and organizational environments. Drawing on the UTAUT2 framework, this research employs a quantitative method involving 129 Indonesian respondents from Generations Y and Z. Data were collected via structured questionnaires and analyzed using SmartPLS to examine the relationships among key variables. The study contributes to AI adoption literature by contextualizing behavioral technology acceptance within the Southeast Asian user base. Its novelty lies in examining ChatGPT use not only as a technological trend, but also as a cognitive and habitual practice. Managerially, the insights benefit AI developers, educators, and institutional leaders by helping them foster sustainable usage through accurate content delivery and reinforcement of positive user habits. The findings aim to provide insight into the factors driving ChatGPT adoption and broader adoption trends in decision-making within the management field.